2021
DOI: 10.1038/s41419-021-03466-5
|View full text |Cite
|
Sign up to set email alerts
|

c-MYC-induced long noncoding RNA MEG3 aggravates kidney ischemia–reperfusion injury through activating mitophagy by upregulation of RTKN to trigger the Wnt/β-catenin pathway

Abstract: Ischemia–reperfusion injury (IRI)-induced acute kidney injury (AKI) is a life-threatening disease. The activation of mitophagy was previously identified to play an important role in IRI. Maternally expressed 3 (MEG3) can promote cerebral IRI and hepatic IRI. The present study was designed to study the role of MEG3 in renal IRI. Renal IRI mice models were established, and HK-2 cells were used to construct the in vitro models of IRI. Hematoxylin–eosin staining assay was applied to reveal IRI-triggered tubular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 55 publications
1
47
0
Order By: Relevance
“…miR-145-5p has been reported to be dysregulated and involved in kidney injuries. 17 , 18 To determine whether supplement of miR-145-5p could alleviate kidney injury in mouse models, we purified the EVs from miR-145-5p transfected Jurkat or HEK293 cells and obtained the miR-145-5p-enriched EVs ( Figure S1 ). We first tested the miR-145-5p EV samples for toxicity or side effects on healthy control mice by administering miR-145-5p EVs intravenously every other day for a total of 3 times.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-145-5p has been reported to be dysregulated and involved in kidney injuries. 17 , 18 To determine whether supplement of miR-145-5p could alleviate kidney injury in mouse models, we purified the EVs from miR-145-5p transfected Jurkat or HEK293 cells and obtained the miR-145-5p-enriched EVs ( Figure S1 ). We first tested the miR-145-5p EV samples for toxicity or side effects on healthy control mice by administering miR-145-5p EVs intravenously every other day for a total of 3 times.…”
Section: Resultsmentioning
confidence: 99%
“…miR-145-5p dysregulation has been shown to be involved in kidney injury by mediating the effect of MALAT1 17 and MEG3 18 on kidney. Recently, we investigated whether systemically administered miR-145-5p could mitigate kidney injury in mouse models, and, unexpectedly, we found that treatment of normal control mice with extracellular vesicles (EVs) loaded with miR-145-5p resulted in albuminuria and podocyte foot process effacement.…”
Section: Introductionmentioning
confidence: 99%
“…Construction of ALI model miR-145-5p expression is decreased in renal ischemia-reperfusion injury [29], and ETS2 is up-regulated in ARDS [14]. miR-145-5p, ETS2, TGF-β1 and Smad2/3 levels, as well as the phosphorylated (p)-Smad2/3 in rats with ALI were detected by RT-qPCR and Western blot.…”
Section: Resultsmentioning
confidence: 99%
“…Through GO and KEGG analysis, identified the main biological function of Co-DE mRNAs. There are several signaling pathways involved in ischemia-reperfusion injury, including Wnt signaling pathway, 34 PI3K/Akt signaling pathway, 35 JAK/STAT signaling pathway, 32 and cAMP signaling pathway 36 among others. The result of KEGG analysis verified the association of Co-DE mRNAs with the above signaling pathways, such as cAMP pathway and PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%